Effects of various drilling parameters on bone during implantology: An in vitro experimental study - Karaca, Faruk; Aksakal, Bunyamin (Wroclaw Univ Technology, Fac Computer Science & Management, 2013)
Due to temperature increase during bone drilling, bone necrosis is likely to occur. To minimize bone tissue damage during drilling, a detailed in vitro experimental study by using fresh calf cortical bones has been performed with various combined drilling parameters, such as: drilling environment, drill diameter, drill speed, drill force, feed-rate and drill coating. Bone temperatures at the drilling sites were recorded with high accuracy using multi-thermocouples mounted around the tibial diaphyseal cortex. It was shown that temperatures increased with increased drill speeds. It also decreased with a higher feed-rate and drill force. It was also observed that TiBN coated drills caused higher temperatures in the bone than the uncoated drills and the temperatures increased with larger drill diameters. Although the influence of Simulated Body Fluid (SBF) on rising temperatures during drilling was higher for the TiBN coated drills, it was observed that these drills caused more damage to the bone structure. In order to minimize or avoid bone defects and necrosis, orthopaedic surgeons should consider the optimum drilling parameters.
Keywords: orthopaedics; bone drilling; temperature; bone necrosis